Entrepreneurship of farmers in Poland − the current situation and development trends - Rak, Anna Maria; Multan, Ewa (Management and Administration Journal, 2024)
Currently, the economic growth in rural areas in Poland depends, to a large extent, on the development of various forms of entrepreneurship. Due to the increasing difficulties that the traditional sectors of the rural economy are facing, the future success of rural residents is inextricably linked to the search for new business opportunities. They can constitute an additional source of income for farmers, as well as positively improve the living conditions of the rural population and help achieving local development goals. In this study, entrepreneurship of farmers was discussed on the example of nonagricultural economic activities, which is recognized as directly related to farming, i.e. using its resources (labour, land, buildings, machinery). It does not include any activity other than farming, only when labour is used as the resource of the farm to perform the work. The main objective of the study was to recognize the scale of the phenomenon and directions of development of non-agricultural activity in Poland and make the characteristics of the farms undertaking this type of activity.